Job compatibility among kindergarten principals in the State of Kuwait from the teachers' point of view - Al-Hearz, Amna Haidar (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of achieving job compatibility among kindergarten principals in the State of Kuwait from The teachers' point of view, and the study adopted the descriptive survey method, and the researchers prepared a questionnaire to measure The degree of achieving functional compatibility, and the study sample consisted of (400) female teachers, who were chosen by random method Relative, by (%11),The results of the study showed that the degree of achieving functional compatibility as a whole came to a (significant) degree; The results also showed that there were no statistically significant differences at the level of statistical significance (= 0.05) between the responses of the study sample members in the degree of achieving functional compatibility among the principals of kindergartens in the State of Kuwait from the point of view of the teachers due to the variables (age, educational qualification, and the children’s years from In order to achieve sustainable development experience, and educational stage). The study recommended spreading a culture of job compatibility among workers in Riyadh.
Keywords: job compatibility; kindergarten; Kuwait